The electoral consequences of the coal phase-out in Germany - Sophia Stutzmann (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2024)
Climate policies can have adverse social and economic effects on affected citizens. Against this backdrop, understanding the conditions under which electoral support or backlash to such policies occurs is crucial. In this paper, I set out to shed light on this issue by empirically analysing the electoral repercussions of the coal phase-out in Germany. By employing a series of fixed-effects models, I investigate whether the closures of coal plants and mines between 2007 and 2022 affected voting behaviour at the municipality level. I find that closures result in lower vote shares for the Social Democratic Party and higher abstention rates in affected municipalities. These findings document a punishment of the long-time issue owner and point towards the role of economic grievances in curbing political engagement. With the high politicisation around the issue of fossil fuel energy generation, these findings have important implications for the remaining coal phase-outs worldwide.
urn:nbn:de:bsz:352-2-1ouknqxwjvwg16
Keywords: 320